Consequences of inaccurate hepatitis C virus genotyping on the costs of prescription of direct antiviral agents in an Italian district - Polilli E; Cento V; Restelli U; Ceccherini-Silberstein F; Aragri M; Di Maio VC; Sciacca A; Santoleri F; Fazii P; Costantini A; Perno CF; Parruti G (Dove Medical Press, 2016)
Ennio Polilli,1 Valeria Cento,2 Umberto Restelli,3,4 Francesca Ceccherini-Silberstein,2 Marianna Aragri,2 Velia Chiara Di Maio,2 Antonina Sciacca,1 Fiorenzo Santoleri,5 Paolo Fazii,6 Alberto Costantini,5 Carlo Federico Perno,2 Giustino Parruti1 1Infectious Diseases Unit, Pescara General Hospital, Pescara, 2Department of Experimental Medicine and Surgery, University of Rome “Tor Vergata”, Rome, 3CREMS - Centre for Research on Health Economics, Social and Health Care Management, Carlo Cattaneo – LIUC University, Castellanza, Italy; 4School of Public Health, Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, South Africa; 5Hospital Pharmacy, Pescara General Hospital, 6Microbiology and Virology Unit, Pescara General Hospital, Pescara, Italy Abstract: Available commercial assays may yield inaccurate hepatitis C virus (HCV) genotype assignment in up to 10% of cases. We investigated the cost-effectiveness of re-evaluating HCV genotype by population sequencing, prior to choosing a direct acting antiviral (DAA) regimen. Between March and September 2015, HCV sequence analysis was performed in order to confirm commercial LiPA-HCV genotype (Versant® HCV Genotype 2.0) in patients eligible for treatment with DAAs. Out of 134 consecutive patients enrolled, sequencing yielded 21 (15.7%) cases of discordant results. For three cases of wrong genotype assignment, the putative reduction in efficacy was gauged between 15% and 40%. Among the eight cases for whom G1b was assigned by commercial assays instead of G1a, potentially suboptimal treatments would have been prescribed. Finally, for five patients with G1 and indeterminate subtype, the choice of regimens would have targeted the worst option, with a remarkable increase in costs, as in the case of the four mixed HCV infections for whom pan-genotypic regimens would have been mandatory. Precise assignment of HCV genotype and subtype by sequencing may, therefore, be more beneficial than expected, until more potent pan-genotypic regimens are available for all patients. Keywords: HCV, HCV sequence analysis, HCV genotype, direct acting antiviral, treatment costs